Digital Archive for Nutrition-Sensitive Projects in Cambodia: A Twenty-Year Retrospective and Resource Compilation - Ou, Phichong (2025)
This document compiles a collection of key materials, including Information, Education, and Communication (IEC) materials, training manuals, guidelines, policies, strategies, and reports, developed and implemented by various Food Security and Nutrition-Sensitive Projects in Cambodia over the past 20 years. These existing resources outline practical approaches and methodologies for food security and nutrition-sensitive interventions, offering valuable insights and strategies that can be adapted for future relevant projects.